Benchmarking working Europe 2016 (Brussels, 2016)
"With this year’s chosen focus – ‘prepared for the future?’ – the new edition of Benchmarking working Europe analyses the state of working Europe with the aid of a multi-level and multi-dimensional set of indicators.